2021
DOI: 10.7595/management.fon.2021.0031
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Factors of Customer Loyalty Formation for Wellness Spa

Abstract: Research question: The objective of this paper is to examine the level of the development of spa tourism with a special review of the wellness tourist offer of the Republic of Serbia, and also which factors of this tourist offer we should pay special attention to and improve, to achieve the highest level of tourist loyalty. Motivation: The tourism potential of the Republic of Serbia has not been sufficiently researched and that served as a basic motivational factor. Idea: Considering the tourist potential that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…a psychological state of pleasure closely linked to the five senses. The hedonic experience associated with F&B is reflected in the pleasure derived from what one eats and drinks; in this sense, several authors have identified how tourists' visits to specific wellness and spa resort and destinations are characterized by this type of experience (Lakićević et al. , 2021; Kiatkawsin and Han, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…a psychological state of pleasure closely linked to the five senses. The hedonic experience associated with F&B is reflected in the pleasure derived from what one eats and drinks; in this sense, several authors have identified how tourists' visits to specific wellness and spa resort and destinations are characterized by this type of experience (Lakićević et al. , 2021; Kiatkawsin and Han, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…a psychological state of pleasure closely linked to the five senses. The hedonic experience associated with F&B is reflected in the pleasure derived from what one eats and drinks; in this sense, several authors have identified how tourists' visits to specific wellness and spa resort and destinations are characterized by this type of experience (Laki cevi c et al, 2021;Kiatkawsin and Han, 2017). In this logic, alcohol consumption is also depicted as a hedonic, short-lived and relaxing experience (Kim and Yang, 2021), which is why wine consumption can also positively impact the well-being of tourists (Kotur, 2022;Fiore et al, 2019).…”
Section: Fandb In the Wellness Experiencementioning
confidence: 99%
“…Ranking using preferences is the most commonly used method in making multi-criteria decisions (Durkalić et al, 2019;Lakićević et al, 2021). Expert assessment is the use of expert knowledge in order to predict future conditions, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Rural settlements become an attractor for tourists, especially in conditions when there was a pandemic, and the local population was looking for a place to escape from urban areas, and to avoid closure during the restrictive measures that had to be observed in certain periods of the previous two and a half years (Blešić et al, 2022). However, foreign tourists are also looking for vacations in rural areas, especially those that are poorly explored and have different natural beauty than what has already been seen in Europe and the world (Kirolova and Hamarnech, 2017; Lakićević et al, 2023). Therefore, Serbia has a huge potential for the future of tourism development, primarily by offering untouched rural areas, where, in addition to enjoying nature, tourists can get to know the tradition, culture, history of the Serbian people and all minorities in this area, but also participate in rural activities provided by rural households (Gajić et al,2022a,c,d).…”
Section: Literature Reviewmentioning
confidence: 99%